2020
DOI: 10.1021/acs.cgd.9b01103
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Dynamics of a Continuous Sonicated Tubular Cooling Crystallizer

Abstract: For the first time, continuous ultrasound-assisted tubular crystallizer dynamics has been studied in pilot scale operation. It is vital to understand the process dynamics for continuous crystallizers as robust crystallization processes are developed. The mixing time using tracer impulses and experimental continuous crystallization runs to understand the performance of process variables, with focused beam reflectance measurement (FBRM), process video microscope measurements, and off-line particle size analytics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…They also found that supersaturations that are punctual high and not uniformly distributed lead to clogging. In the case of Ezeanowi et al [60], no clogging was observed at similar average velocities of 5-9 cm s − 1 and an internal diameter of 250 mm. The observed duration per experiment was also 3-4 residence times [60].…”
Section: Pressure Drop and Cloggingmentioning
confidence: 80%
See 3 more Smart Citations
“…They also found that supersaturations that are punctual high and not uniformly distributed lead to clogging. In the case of Ezeanowi et al [60], no clogging was observed at similar average velocities of 5-9 cm s − 1 and an internal diameter of 250 mm. The observed duration per experiment was also 3-4 residence times [60].…”
Section: Pressure Drop and Cloggingmentioning
confidence: 80%
“…In the case of Ezeanowi et al [60], no clogging was observed at similar average velocities of 5-9 cm s − 1 and an internal diameter of 250 mm. The observed duration per experiment was also 3-4 residence times [60].…”
Section: Pressure Drop and Cloggingmentioning
confidence: 80%
See 2 more Smart Citations
“…Ultrasound assistance in mixing during tubular crystallization, besides eliminating pipe clogging, helps to control crystal size as well. 22 The production of active pharmaceutical ingredients via flow chemistry has led to the syntheses of many promising compounds. 23 Metal ions in the form of sparingly soluble salts can also be spatially separated from their homogeneous solution mixture by the appropriate choice of precipitation.…”
Section: Introductionmentioning
confidence: 99%